Compassionate conservatism vs Bush doctrine - Soltani, Fakhreddin; Jawan, Jayum (Canadian Academy of Oriental and Occidental Culture, 2010)
George W. Bush compared his administration plan for Pre-September the 11th with Post-September the 11th and declared that the first one was designed for internal issues such as helping parents, developing good character in American children, and strengthening a spirit of citizenship and service in the United States; but the second era changed the ways that was planed for past. Defeating evildoers and bringing them to justice shaped the way United States has to pass. In contrast to pre-September the 11th which had been called conditions of peace; the new condition after September the 11th was recognised as war condition and was declared as necessary war that is necessity of United States’ future security and freedom of American children (Bush, 11 October 2001). This article is to study perspective of George W. Bush and his administration on security strategies of the United States in pre-September the 11th (Compassionate Conservatism) and post-September the 11th era (Bush Doctrine).